Hydrogen storage material and preparation method thereof

By combining fibrous VNbO5 with magnesium hydride (MgH2), the problems of high hydrogen release temperature, slow hydrogen absorption and discharge rate and poor circulation stability of magnesium hydride hydrogen storage materials are solved, and more efficient hydrogen absorption and discharge and better circulation performance are achieved.

CN119637806APending Publication Date: 2025-03-18QINGHAI SALT LAKE IND +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411531905.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The existing magnesium hydride hydrogen storage materials have high hydrogen release temperature, slow hydrogen absorption and release rate, poor circulation stability, and poor catalyst contact with the surface of MgH2 particles, resulting in poor catalytic effect.

Method used

Fibrous VNbO5 is combined with MgH2, and fibrous VNbO5 is prepared by spinning and calcining, and mixed with MgH2 by ball milling to form a hydrogen storage material.

Benefits of technology

It effectively reduces the hydrogen release temperature of magnesium hydride, increases the hydrogen release and hydrogen absorption rate, improves the cycle stability of hydrogen storage materials, and enhances the catalytic effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119637806A_ABST
    Figure CN119637806A_ABST
Patent Text Reader

Abstract

The invention provides a hydrogen storage material and a preparation method thereof, the hydrogen storage material comprises MgH2 and fibrous VNbO5, and the length-diameter ratio of the fibrous VNbO5 is 5.0 * 10 < 4 >-1.15 * 10 < 5 >. In the hydrogen storage material, MgH2 and fibrous bimetallic oxide VNbO5 cooperate with each other, so that the hydrogen desorption kinetics of MgH2 is effectively improved, the hydrogen desorption temperature of magnesium hydride is reduced, the hydrogen desorption rate of MgH2 is increased, the hydrogen absorption kinetics of MgH2 is effectively improved, the hydrogen absorption rate of MgH2 is increased, and fibrous VNbO5 can form good contact with MgH2, so that the hydrogen storage material has good hydrogen desorption performance. The catalytic effect and the cycling stability of the hydrogen storage material are effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of hydrogen storage, and in particular to a hydrogen storage material and a preparation method thereof. Background Art

[0002] Among solid-state hydrogen storage materials, Mg / MgH2 is widely considered to be one of the materials with broad application potential due to its advantages such as high hydrogen storage capacity, low cost and light weight.

[0003] However, the thermodynamic enthalpy change of magnesium hydride is relatively high (ΔH ~ 75 kJ / mol), resulting in its dehydrogenation temperature usually exceeding 300 °C; in addition, the dissociation barrier of H2 on the surface of MgH2 is relatively high and the diffusion rate is relatively slow, resulting in its kinetic rate being limited (activation energy E a During the cycle of hydrogen absorption and desorption, MgH2 / Mg particles usually agglomerate and grow, which further affects the cyclic stability of the material and limits the commercialization of the Mg / MgH2 hydrogen storage system.

[0004] In the prior art, catalysts are valued for their excellent catalytic activity. In particular, composite catalysts exhibit better catalytic performance than single catalysts due to their multiple active sites. However, most current catalyst preparation methods, such as ball milling, although aimed at achieving material mixing, face challenges in interfacial bonding with the Mg / MgH2 hydrogen storage system. During the process of hydrogen absorption and desorption, conventional catalysts are difficult to continuously and stably adhere to the surface of Mg / MgH2 particles, which results in a significant decrease in the catalytic effect. Summary of the invention

[0005] The main purpose of the present invention is to provide a hydrogen storage material and a preparation method thereof, so as to solve the problems in the prior art that the magnesium hydride material has a high dehydrogenation temperature, a slow hydrogen absorption and dehydrogenation rate, and a poor cycle stability, and the catalyst cannot form a good interface contact with MgH2 during the ball milling process, resulting in a poor catalytic effect.

[0006] In order to achieve the above object, according to one aspect of the present invention, a hydrogen storage material is provided, comprising MgH2 and fibrous VNbO5, wherein the aspect ratio of the fibrous VNbO5 is 5.0×10 4 ~1.15×10 5 .

[0007] Further, the diameter of the fibrous VNbO5 is 300 to 1000 nm, preferably 300 to 500 nm; and / or the specific surface area of ​​the fibrous VNbO5 is 89 to 96 m 2 / g.

[0008] Furthermore, in the hydrogen storage material, the weight percentage of fibrous VNbO5 is 3 to 10%.

[0009] Furthermore, when the aspect ratio of fibrous VNbO5 is 5.0×10 4 ~7.35×10 4 When the weight percentage of fibrous VNbO5 in the hydrogen storage material is 5-7%.

[0010] Furthermore, the hydrogen storage material is subjected to hydrogen desorption at an elevated temperature, with an initial hydrogen desorption temperature of 195 to 200.2°C; the hydrogen storage material is subjected to isothermal hydrogen desorption, with a hydrogen desorption rate of 1.01 to 1.62 wt% / min at a hydrogen desorption temperature of 250 to 325°C; the hydrogen storage material is subjected to isothermal hydrogen absorption, with a hydrogen absorption rate of 0.298 to 0.354 wt% / min at a hydrogen absorption temperature of 75 to 125°C; after the hydrogen storage material is subjected to 20 cycles of isothermal hydrogen desorption and 20 cycles of isothermal hydrogen absorption alternately at 300°C, the hydrogen absorption capacity retention rate is 91.6 to 95.3%, and the dehydrogenation capacity retention rate is 93.3 to 99.86%.

[0011] According to another aspect of the present invention, a method for preparing the above-mentioned hydrogen storage material is provided, comprising the following steps: step S1, first mixing a vanadium source, a niobium source and a co-solvent, and sequentially spinning and calcining to obtain fibrous VNbO5; step S2, ball milling MgH2 and fibrous VNbO5 to obtain a hydrogen storage material.

[0012] Further, in step S1, the vanadium source includes one or more of ammonium metavanadate, vanadium pentoxide and vanadium acetylacetonate; and / or, the niobium source includes one or more of niobium oxalate, niobium pentoxide and niobium pentachloride; and / or, the co-solvent includes one or more of oxalic acid, citric acid and acetic acid; and / or, the molar ratio of the vanadium source, the niobium source and the co-solvent is 1:(0.8-1.2):(0.8-1); preferably, step S1 also includes, mixing the vanadium source, the niobium source and the co-solvent for a second time, and then mixing them with the solvent and the stabilizer for a third time to obtain a mixed gel, and spinning and calcining the mixed gel in sequence; more preferably, the solvent includes one or more of water, ethanol, methanol and N,N-dimethylformamide; and / or, the stabilizer includes one or more of PVP, polyvinyl acetate and polyacrylonitrile; further preferably, the solid content of the mixed gel is 8-11wt%.

[0013] Furthermore, in step S1, spinning is electrospinning; preferably, the electrospinning liquid pushing speed is 0.08 to 0.12 mm / min, the applied positive voltage is 18 to 22 kV, the applied negative voltage is -1 to -3 kV, and the receiving distance is 12 to 18 cm.

[0014] Furthermore, in step S1, the calcination temperature is 500-550° C. and the calcination time is 3-5 hours.

[0015] Furthermore, in step S2, the ball milling pressure is 0.3-0.8 MPa; and / or the ball-to-material ratio of the ball milling is (40-60):1; and / or the ball milling speed is 400-450 rpm, and the time is 5-10 h.

[0016] In the hydrogen storage material of the present invention, MgH2 and the fibrous bimetallic oxide VNbO5 cooperate with each other, which not only effectively improves the hydrogen desorption kinetics of MgH2, reduces the hydrogen desorption temperature of magnesium hydride, and increases the hydrogen desorption rate of MgH2, but also effectively improves the hydrogen absorption kinetics of MgH2 and increases the hydrogen absorption rate of MgH2. Moreover, the fibrous VNbO5 can form good contact with MgH2, effectively improving the catalytic effect and cycle stability of the hydrogen storage material.

[0017] In summary, the hydrogen storage material of the present invention has a low hydrogen desorption temperature, a fast hydrogen absorption and desorption rate, and good cycle stability, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0019] Figure 1 shows the XRD pattern of VNbO5 of Example 1 of the present invention;

[0020] Figure 2 shows a SEM image of VNbO5 of Example 1 of the present invention;

[0021] Figure 3 TEM, SEM and EDS images of VNbO5 of Example 1 of the present invention are shown;

[0022] Figure 4 The temperature increase hydrogen release diagram of the hydrogen storage materials of Examples 1 to 4 of the present invention and Comparative Example 1 is shown;

[0023] Figure 5 The isothermal hydrogen release diagrams of the hydrogen storage materials of Example 1 and Comparative Example 1 of the present invention at different temperatures are shown;

[0024] Figure 6 The isothermal hydrogen absorption diagrams of the hydrogen storage materials of Example 1 and Comparative Example 1 of the present invention at different temperatures are shown;

[0025] Figure 7 The isothermal desorption / adsorption cycle curve diagram of the hydrogen storage material of Example 1 of the present invention is shown; wherein the red line represents the isothermal hydrogen desorption curve, and the blue line represents the isothermal hydrogen absorption curve.

[0026] Figure 8The DSC curves and DSC curve peak fitting diagrams of the hydrogen storage materials of Example 1 and Comparative Example 1 of the present invention are shown;

[0027] Fig. 9 The JMA curve and Arrhenius fitting curve of the hydrogen storage materials of Example 1 and Comparative Example 1 of the present invention are shown; and

[0028] Fig.10 The DSC graphs of the hydrogen storage materials of Example 1 and Comparative Example 1 of the present invention are shown. DETAILED DESCRIPTION

[0029] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.

[0030] Terminology explanation:

[0031] Total hydrogen release: the amount of hydrogen that can be released by hydrogen storage materials under certain conditions (such as temperature, pressure, etc.).

[0032] Hydrogen release rate: the amount of hydrogen released from the hydrogen storage material per unit time.

[0033] As described in the background of the present invention, the prior art has the problems that the magnesium hydride material has a high dehydrogenation temperature, a slow hydrogen absorption and dehydrogenation rate, and poor cycle stability, and the catalyst cannot form a good interface contact with MgH2 during the ball milling process, resulting in a poor catalytic effect. In order to solve the above problems, in a typical embodiment of the present invention, a hydrogen storage material is provided, including MgH2 and fibrous VNbO5, the aspect ratio of the fibrous VNbO5 is 5.0×10 4 ~1.15×10 5 .

[0034] The hydrogen storage material of the present application includes MgH2 and a catalyst bimetallic oxide VNbO5. Among them, the vanadium and niobium metals in VNbO5 cooperate with each other, and the high-valent V and Nb metal elements are easily reduced to low-valent or even zero-valent metals, which can create a multi-element, multi-valent chemical environment in situ, form rich grain boundaries with MgH2 / Mg, and provide multiple channels for the diffusion and electron transfer of hydrogen. On the one hand, it can accelerate the electron transfer between Mg and H, weaken the Mg-H bond, reduce the dissociation energy of MgH2, and improve the dehydrogenation kinetics of MgH2, thereby effectively reducing the dehydrogenation temperature of magnesium hydride and increasing the dehydrogenation rate of MgH2; on the other hand, it can increase the catalytic active sites of the hydrogen storage material, improve the catalytic activity, and reduce the dissociation energy of hydrogen molecules on the surface of MgH2, thereby effectively improving the hydrogen absorption kinetics of MgH2 and increasing the hydrogen absorption rate of MgH2.

[0035] The inventor unexpectedly found during the research that although transition metal oxides can be added to MgH2 to improve hydrogen storage materials in the prior art, the commonly used powdered transition metal oxides will not be able to form a good interface contact with the hydrogen storage material Mg / MgH2 during the ball milling process due to their own exposed specific surface area, which is not conducive to the continuous and stable attachment to the Mg / MgH2 particles during the subsequent hydrogen absorption and release process, and the catalytic effect is greatly reduced, thereby making the cycle stability of the hydrogen storage material worse. The present application specifically uses fibrous VNbO5 as a catalyst to improve the hydrogen storage material. Compared with conventional powdered transition metal oxides (such as V-Nb oxide particles), fibrous VNbO5 has a large specific surface area, and a small and uniform particle size, which is not easy to agglomerate and grow. It can form a good interface with Mg / MgH2 during the ball milling process. Full contact, which is beneficial to increase the active sites of MgH2 and the diffusion path of hydrogen, can significantly improve the hydrogen storage performance of MgH2 and improve the cycle stability of the hydrogen storage material.

[0036] In addition, the present application specifically limits the aspect ratio of fibrous VNbO5 to 5.0×10 4 ~1.15×10 5 The VNbO5 has the advantages of uniform size and large exposed specific surface area, which is conducive to forming a good interface contact with Mg / MgH2. However, if the aspect ratio is too small, it may cause material agglomeration and decrease porosity. If the aspect ratio is too large, it may cause the material structure stability to decrease.

[0037] In summary, in the hydrogen storage material of the present application, MgH2 and the fibrous bimetallic oxide VNbO5 work together to not only effectively improve the hydrogen desorption kinetics of MgH2, reduce the hydrogen desorption temperature of magnesium hydride, and increase the hydrogen desorption rate of MgH2, but also effectively improve the hydrogen absorption kinetics of MgH2 and increase the hydrogen absorption rate of MgH2. Moreover, the fibrous VNbO5 can form good contact with MgH2, which is beneficial to effectively improve the catalytic effect and cycle stability of the hydrogen storage material, thereby promoting the development and application of the Mg / MgH2 hydrogen storage system.

[0038] In a preferred embodiment, the diameter of the fibrous VNbO5 is 300 to 1000 nm, preferably 300 to 500 nm; the specific surface area of ​​the fibrous VNbO5 is 89 to 96 m 2 / g. Under the above conditions, the contact area between fibrous VNbO5 and MgH2 is larger, the synergistic effect with MgH2 is better, and it is more conducive to improving the catalytic performance and cycle stability of hydrogen storage materials.

[0039] After a large number of experiments, the inventors found that the addition of VNbO5 can significantly reduce the dehydrogenation temperature of MgH2, and as the amount of VNbO5 added increases, the dehydrogenation temperature of the hydrogen storage material decreases. However, when the amount of VNbO5 added is too high, although the initial dehydrogenation temperature of the hydrogen storage material is effectively reduced, the effective hydrogen storage capacity will be reduced to a certain extent. In order to take into account the dehydrogenation temperature, dehydrogenation amount and dehydrogenation rate, the inventors have specially optimized the addition amount of VNbO5. In a preferred embodiment, the weight percentage of fibrous VNbO5 in the hydrogen storage material is 3-10%. Under the above conditions, the comprehensive dehydrogenation performance of the hydrogen storage material is better, not only more effectively reducing the initial dehydrogenation temperature of the hydrogen storage material, but also the total amount of dehydrogenation and the dehydrogenation rate are higher.

[0040] In a preferred embodiment, when the aspect ratio of the fibrous VNbO5 is 5.0×10 4 ~7.35×10 4 When the weight percentage of fibrous VNbO5 in the hydrogen storage material is 5-7%.

[0041] Those skilled in the art know that, under a standard atmospheric pressure, MgH2 can only be decomposed at a temperature higher than 287°C (theoretical value), and in actual situations, in order to dehydrogenate more thoroughly, it is generally necessary to heat to about 350°C. As mentioned above, the present application specifically introduces the catalyst VNbO5 to significantly reduce the operating temperature of MgH2, and quickly absorb / release as much hydrogen as possible at the lowest possible temperature in a shorter time. In a preferred embodiment, the hydrogen storage material is heated to dehydrogenate, and the initial dehydrogenation temperature is 195-200.2°C; the hydrogen storage material is isothermally dehydrogenated, and the dehydrogenation rate is 1.01-1.62wt% / min under the condition of the dehydrogenation temperature of 250-325°C; the hydrogen storage material is isothermally absorbed hydrogen, and the hydrogen absorption rate is 0.298-0.354wt% / min under the condition of the hydrogen absorption temperature of 75-125°C.

[0042] At present, the widely accepted and adopted enthalpy of formation of MgH2 is 74.7 kJ / mol H2. Such a high enthalpy of formation makes MgH2 have a high thermodynamic stability, so that its operating temperature is relatively high in practical applications. However, each stage of the hydrogen absorption / desorption process of the MgH2 system needs to overcome a high potential barrier, which makes the hydrogen absorption and desorption rate of MgH2 slow. The activation energy and reaction enthalpy of the hydrogen absorption / desorption reaction serve as a standard for evaluating the kinetics and thermodynamics of the hydrogen storage system. The magnitude of their values ​​directly reflects the kinetic performance and operating temperature of the hydrogen absorption / desorption of the MgH2 system. As mentioned above, in the hydrogen storage material of the present application, the addition of fibrous VNbO5 is beneficial to effectively reduce the activation energy and reaction enthalpy of MgH2. In a preferred embodiment, the activation energy of the hydrogen storage material is E a(des)=75.32~87.9kJ / mol, the activation energy of catalytic hydrogen absorption is E a(abs) =54.4~66.7kJ / mol; desorption reaction enthalpy change ΔH=73.26~76.54kJ / mol.

[0043] During multiple cycles of hydrogen absorption and desorption, MgH2 / Mg particles are very likely to agglomerate and grow, resulting in a decrease in the specific surface area of ​​the particles, a decrease in active sites, and a gradual slowdown in the rate of hydrogen absorption and desorption. Moreover, the MgH2 / Mg inside the agglomerate is difficult to participate in the process of hydrogen absorption and desorption, resulting in a gradual attenuation of the hydrogen storage capacity, thereby reducing the cycle stability. As mentioned above, in the hydrogen storage material of the present application, the addition of fibrous VNbO5 can effectively inhibit the agglomeration and growth of MgH2 / Mg particles, which is beneficial to improving the hydrogen storage performance and cycle stability of MgH2. After multiple cycles, the hydrogen storage capacity of the hydrogen storage material of the present application has no obvious loss, the capacity retention rate is ≥99%, and the hydrogen absorption and desorption kinetics remain at the original level. In a preferred embodiment, after the hydrogen storage material is alternately cycled at 300°C for 20 isothermal hydrogen releases and 20 isothermal hydrogen absorptions, the hydrogen absorption capacity retention rate is 91.6-95.3%, and the dehydrogenation capacity retention rate is 93.3-99.86%.

[0044] In another typical embodiment of the present invention, a method for preparing the above-mentioned hydrogen storage material is also provided, comprising the following steps: step S1, first mixing a vanadium source, a niobium source and a solvent, and sequentially spinning and calcining to obtain fibrous VNbO5; step S2, ball milling MgH2 and fibrous VNbO5 to obtain a hydrogen storage material.

[0045] In the prior art, VNbO5 is usually prepared according to a hydrothermal method or a sol-gel method, which has the advantage of a simple preparation process, but its material morphology is difficult to control and the specific surface area of ​​the obtained material is small, resulting in poor kinetic performance of the composite hydrogen storage system. In view of this, the inventors have made special technical improvements. In the present application, VNbO5 is prepared according to spinning and calcination. The precursor obtained by spinning is small in size and has a uniform particle size distribution. After calcination, impurities and volatile components in the precursor are removed to obtain a fibrous bimetallic oxide VNbO5. Moreover, compared with other oxidation methods, such as adding an oxidant, the calcination method of the present application does not introduce impurities, but directly oxidizes the precursor. The prepared VNbO5 has high purity, and the processing method is simple, involving fewer steps, which is conducive to actual production.

[0046] The VNbO5 prepared by spinning and calcining has the characteristics of uniform size and small specific surface area, and is evenly dispersed in the MgH2 matrix, which is conducive to its catalytic effect. At the same time, during the ball milling process, the mechanical force can significantly refine the grain size of MgH2, increase its specific surface area and surface energy, and thus facilitate the diffusion of hydrogen.

[0047] In summary, the preparation method of the present application is simple to operate, has low energy consumption and less pollution during the reaction process, fewer processes and a short reaction cycle, and the raw materials are easily available, which is convenient for practical operation.

[0048] In order to make the preparation process of VNbO5 more stable and to facilitate the preparation of VNbO5 with a large specific surface area and high purity, in a preferred embodiment, in step S1, the vanadium source includes one or more of ammonium metavanadate, vanadium pentoxide and vanadium acetylacetonate; and / or, the niobium source includes one or more of niobium oxalate, niobium pentoxide and niobium pentachloride; and / or, the co-solvent includes one or more of oxalic acid, citric acid and acetic acid; and / or, the molar ratio of the vanadium source, the niobium source and the co-solvent is 1:(0.8-1.2):(0.8-1); preferably, step S1 also includes a second mixing of the vanadium source, the niobium source and the co-solvent, and then a third mixing with the solvent and the stabilizer to obtain a mixed gel, and the mixed gel is spun and calcined in sequence; more preferably, the solvent includes one or more of water, ethanol, methanol and N,N-dimethylformamide; and / or, the stabilizer includes one or more of PVP, polyvinyl acetate and polyacrylonitrile; further preferably, the solid content of the mixed gel is 8-11wt%. In this process, the vanadium source and the niobium source, as the sources of V and Nb elements respectively, react chemically with the co-solvent and the stabilizer to prepare VNbO5.

[0049] In a preferred embodiment, in step S1, spinning is electrostatic spinning; the spinning solution pushing speed of electrostatic spinning is 0.08-0.12 mm / min, the applied positive voltage is 18-22 kV, the applied negative voltage is -1-3 kV, the receiving distance is 12-18 cm, and in a preferred embodiment, the receiver is a stainless steel drum. Under the above conditions, the preparation process is more stable, the diameter of VNbO5 is more uniform, and the contact with MgH2 is more sufficient.

[0050] In a preferred embodiment, the calcination temperature is 500-550°C and the time is 3-5h. If the calcination temperature is too high, the precursor is prone to fracture and collapse, forming irregular short and thick rod-shaped products, which are difficult to form good contact with Mg / MgH2 during ball milling, and the kinetic properties of the hydrogen storage material are easily deteriorated; if the calcination temperature is too low, there may be impurity phases, and the presence of impurity phases reduces the actual catalytic substance content, which is also easy to deteriorate the kinetic properties. In addition, if the calcination process lasts too long, it is easy to cause the sample crystallinity to decrease, and may cause serious sintering, and even destroy the original crystal structure, thereby affecting the catalytic effect of the hydrogen storage material; on the contrary, if the calcination time is too short, it may lead to insufficient calcination, incomplete decomposition of the precursor, affecting the purity of the calcined product, and further affecting the kinetic properties of the material. At the same time, if the calcination time is too short, it may also lead to a low crystallinity of the material, which ultimately affects the kinetic properties of the material.

[0051] In a preferred embodiment, the ball milling pressure is 0.3-0.8 MPa, and preferably, the ball milling atmosphere is hydrogen. Under the above conditions, the raw material purity is higher and the hydrogen storage capacity of the hydrogen storage material is higher.

[0052] In a preferred embodiment, the ball-to-material ratio of ball milling is (40-60):1; and / or, the rotation speed of ball milling is 400-450rpm, and the time is 5-10h. Under the above conditions, the particle size of the hydrogen storage material is smaller, the specific surface area is larger, and the hydrogen storage capacity is higher. However, if the ball-to-material ratio is too high, the rotation speed is too fast, or the ball milling time is too long, the particle size of the obtained material will be smaller, its surface area will be larger, and the surface energy will be higher. Grain growth and particle agglomeration may occur during the absorption and release of hydrogen, resulting in rapid decay of hydrogen storage capacity and insufficient cycle stability. On the contrary, if the ball-to-material ratio is too low, the rotation speed is too slow, or the ball milling time is too short, the size of the MgH2 particles may not be fully refined, the specific surface area is relatively small, which may be unfavorable for the diffusion of hydrogen atoms and the adsorption of H2 molecules. Moreover, insufficient ball milling may cause VNbO5 to be dispersed unevenly in MgH2, ultimately limiting the catalytic effect.

[0053] Typically but not limiting, in the hydrogen storage material, the weight percentage of VNbO5 is 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% or a range consisting of any two of them.

[0054] Typically but not limiting, the calcination temperature is 500°C, 525°C, 550°C or a range consisting of any two of them; the calcination time is 3h, 4h, 5h or a range consisting of any two of them.

[0055] Typically but not limiting, the ball-to-material ratio of the ball mill is 40:1, 50:1, 60:1 or a range consisting of any two of them; the rotation speed of the ball mill is 400rpm, 425rpm, 450rpm or a range consisting of any two of them; the time is 5h, 6h, 7h, 8h, 9h, 10h or a range consisting of any two of them.

[0056] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.

[0057] Example 1

[0058] A hydrogen storage material, the preparation method of which comprises the following steps:

[0059] (1) Preparation of VNbO5 precursor solution: 0.117 g of ammonium metavanadate, 0.538 g of niobium oxalate and 0.09 g of oxalic acid were weighed respectively, and 10 ml of water was added to fully dissolve the three compounds. Then 10 ml of ethanol was added and stirred to form a mixed solution. Then 1 g of polyvinyl pyrrolidone (M W =1300000), the weight percentage of solid components in the obtained mixed gel is 8.89%, and stirring is continued for 24h to obtain a transparent and viscous sol.

[0060] (2) Preparation of VNbO5 precursor: The precursor solution obtained in step (1) was injected into a syringe (equipped with a 22G stainless steel needle) by electrospinning, and a stainless steel mesh was used as a receiving screen. The spinning solution was pushed at a speed of 0.1 mm / min, and spinning was performed under the conditions of a positive voltage of 20 kV, a negative voltage of -2 kV, and a receiving distance of 15 cm to obtain a film-shaped spinning precursor.

[0061] (3) Preparation of VNbO5: The film-like spinning precursor obtained in step (2) was placed in an oven at 80°C and dried for 12 hours. After drying, it was placed in a muffle furnace and calcined at 500°C for 3 hours to obtain VNbO5.

[0062] (4) Preparation of hydrogen storage material: 0.07 g of VNbO5 obtained in step (3) and 0.93 g of magnesium hydride, wherein the VNbO5 doping amount is 7 wt%, are mixed, and ball milling is performed under the conditions of hydrogen atmosphere, pressure of 0.5 MPa, ball-to-material ratio of 50:1, ball milling speed of 450 r / min, and ball milling time of 5 h to obtain a hydrogen storage material with a doping amount of 7 wt%.

[0063] Example 2

[0064] The only difference from Example 1 is:

[0065] The doping amount of VNbO5 is different. Specifically, in step (4), the doping amount of VNbO5 in the hydrogen storage material is 3 wt%, that is, 0.03 g of VNbO5 obtained in step (3) and 0.97 g of MgH2 are weighed.

[0066] Example 3

[0067] The only difference from Example 1 is:

[0068] The doping amount of VNbO5 is different. Specifically, in step (4), the doping amount of VNbO5 in the hydrogen storage material is 5 wt%, that is, 0.05 g of VNbO5 obtained in step (3) and 0.95 g of MgH2 are weighed.

[0069] Example 4

[0070] The only difference from Example 1 is:

[0071] The doping amount of VNbO5 is different. Specifically, in step (4), the doping amount of VNbO5 in the hydrogen storage material is 10wt%, that is, 0.1g of VNbO5 obtained in step 3 and 0.9g of MgH2 are weighed.

[0072] Example 5

[0073] The difference from Example 1 is that the preparation conditions of VNbO5 in the hydrogen storage material are different, as follows:

[0074] (1) Preparation of VNbO5 precursor solution: 0.117 g of ammonium metavanadate, 0.538 g of niobium oxalate and 0.072 g of oxalic acid were weighed respectively, and 10 ml of water was added to fully dissolve the three compounds. Then 10 ml of ethanol was added and stirred to form a mixed solution. Then 0.87 g of polyvinyl pyrrolidone (M W =1300000), controlling the weight percentage of the solid component of the sol to 8.19%, stirring continuously for 12 h to obtain a transparent and viscous sol.

[0075] (2) Preparation of VNbO5 precursor: The precursor solution obtained in step (1) was injected into a syringe (equipped with a 21G stainless steel needle) by electrospinning, and a stainless steel mesh was used as a receiving screen. The spinning solution was pushed at a speed of 0.08 mm / min, and spinning was performed under the conditions of positive voltage 18 kV, negative voltage -1 kV, and receiving distance 12 cm to obtain a film-shaped spinning precursor.

[0076] (3) Preparation of VNbO5: The film-like spinning precursor obtained in step (2) was placed in a 60°C oven and dried for 12 h. After drying, it was placed in a muffle furnace and calcined at 500°C for 3 h to obtain VNbO5.

[0077] Example 6

[0078] The difference from Example 1 is that the preparation conditions of VNbO5 in the hydrogen storage material are different, as follows:

[0079] (1) Preparation of VNbO5 precursor solution: 0.117 g of ammonium metavanadate, 0.538 g of niobium oxalate and 0.9 g of oxalic acid were weighed respectively, and 10 ml of water was added to fully dissolve the three compounds. Then 15 ml of ethanol was added and stirred to form a mixed solution. Then 1.09 g of polyvinyl pyrrolidone (M W =1300000), controlling the weight percentage of the solid component of the sol to be 10.8%, stirring continuously for 24 hours to obtain a transparent and viscous sol.

[0080] (2) Preparation of VNbO5 precursor: The precursor solution obtained in step (1) was injected into a syringe (equipped with a 23G stainless steel needle) by electrospinning, and a stainless steel mesh was used as a receiving screen. The spinning solution was pushed at a speed of 0.12 mm / min, and spinning was performed under the conditions of a positive voltage of 22 kV, a negative voltage of -3 kV, and a receiving distance of 18 cm to obtain a film-shaped spinning precursor.

[0081] (3) Preparation of VNbO5: The film-like spinning precursor obtained in step (2) was placed in an oven at 80°C and dried for 24 hours. After drying, it was placed in a muffle furnace and calcined at 550°C for 5 hours to obtain VNbO5.

[0082] Comparative Example 1

[0083] The only difference from Example 1 is that the hydrogen storage material contains only 1 g of MgH2 and does not contain VNbO5.

[0084] Comparative Example 2

[0085] The only difference from Example 1 is that V2O5 is used instead of VNbO5.

[0086] The analysis shows that doping with 7wt% V2O5 can reduce the initial dehydrogenation temperature of MgH2 from 322.2℃ to 237.2℃, which is higher than 200.2℃ under VNbO5 catalysis; at 300℃, it takes 27min to release 6wt% hydrogen; at 200℃, the amount of hydrogen absorbed within 1min is only 4.86wt%. Whether it is the initial dehydrogenation temperature or the hydrogen absorption and dehydrogenation reaction rate, MgH2 with V2O5 added is worse than MgH2 with VNbO5 added.

[0087] Comparative Example 3

[0088] The only difference from Example 1 is that Nb2O5 is used instead of VNbO5.

[0089] The analysis shows that the addition of 7wt% Nb2O5 reduces the initial hydrogen release temperature of MgH2 from 322.2℃ to 240.7℃, which is much higher than 200.2℃ under VNbO5 catalysis; at 300℃, it takes about 60min to release 6wt% hydrogen; at 200℃, the amount of hydrogen absorbed within 1min is only 1.06wt%. The hydrogen storage performance of this composite material is significantly inferior to that of MgH2 with VNbO5 added.

[0090] Comparative Example 4

[0091] For the scheme of the paper “Remarkable hydrogen storage properties of MgH2 doped with VNbO5”, see https: / / doi.org / 10.1039 / C7CP07157D.

[0092] It can be seen from the analysis that the article prepared VNbO5 as a catalyst for MgH2 by a solid-state method. The desorption temperature of MgH2 doped with VNbO5 samples was significantly reduced from 330°C to 235°C. In addition, at 160°C, under 20 bar of hydrogen, more than 5wt% of hydrogen can be absorbed within 5 minutes. However, the catalytic activity of this catalyst is significantly lower than that of VNbO5 prepared by electrospinning technology in the examples of this application.

[0093] Comparative Example 5

[0094] For the scheme of the paper “Hydrogen storage properties of MgH2 modified by efficient Co3V2O8catalyst”, see https: / / doi.org / 10.1016 / j.seppur.2024.126901.

[0095] According to the analysis, the article prepared Co3V2O8 nanosheets as a catalyst. At 100°C, MgH2-Co3V2O8 absorbed 3.89wt% of hydrogen in 30 minutes. At 300°C, it took 5 minutes to release 5.94wt% of hydrogen. After 30 cycles, the hydrogen release capacity of the MgH2-Co3V2O8 composite material was only 4.35wt%, and the capacity retention rate was only 73%. It can be seen that the catalytic effect of Co-V bimetallic oxide is significantly worse than that of V-Nb bimetallic oxide in the embodiment of the present application.

[0096] The XRD pattern of VNbO5 prepared in Example 1 is as follows: Figure 1As shown in FIG. 1 , the diffraction peaks of VNbO5 are well consistent with the crystal plane of the standard card (PDF#46-0046), with high purity and high crystallinity, indicating that VNbO5 has been successfully synthesized. Figure 2 As shown, VNbO5 is in nanofilament form, with a rough surface and textures, and is well distributed in the range of 300 to 500 nm. The TEM, SEM and EDS images of VNbO5 prepared in Example 1 are shown in FIG. Figure 3 As shown, 3A represents the TEM image of VNbO5, 3B represents the TEM image of VNbO5, 3C represents the HRTEM image of VNbO5, 3D represents the SEM image of VNbO5, 3E represents the V element distribution of VNbO5 in the EDS image, 3F represents the Nb element distribution of VNbO5 in the EDS image, and 3G represents the O element distribution of VNbO5 in the EDS image. The EDS spectrum shows that VNbO5 has only three elements: V, Nb, and O. From the TEM data, it can be seen that the lattice spacing of the filamentous VNbO5 is about 0.226nm, which is consistent with the (103) plane of VNbO5 (PDF#46-0046).

[0097] The temperature increase hydrogen release diagram of the hydrogen storage materials obtained in Examples 1 to 4 and Comparative Example 1 is as follows: Figure 4As shown. Analysis shows that the initial dehydrogenation temperature of the hydrogen storage material of Comparative Example 1 is 322.2°C, and the amount of hydrogen released when the temperature rises to 400°C is 7.293wt%, and the dehydrogenation rate reaches 96% of the theoretical value. Example 1 can reduce the initial dehydrogenation temperature of MgH2 from 322.2°C to 200.2°C by doping 7wt% VNbO5, with a temperature difference of 122°C, and the amount of hydrogen released when the temperature rises to 400°C is 7.02wt%, and the dehydrogenation rate reaches 92.4% of the theoretical value. The initial dehydrogenation temperature of the hydrogen storage material in Example 2 is 206.3°C. When the temperature is raised to 400°C, the dehydrogenation amount is 7.22wt%, and the dehydrogenation rate reaches 95% of the theoretical value. Compared with Comparative Example 1, it can be seen that doping with 3wt% VNbO5 can reduce the initial dehydrogenation temperature of MgH2 from 322.2°C to 206.3°C, a decrease of 115.9°C; compared with Example 1, it can be seen that increasing the VNbO5 doping amount can reduce the initial dehydrogenation temperature from 206.3°C to 200.2°C, a decrease of 6.1°C. The initial dehydrogenation temperature of the hydrogen storage material in Example 3 is 202.6°C. When the temperature is raised to 400°C, the dehydrogenation amount is 7.05wt%, and the dehydrogenation rate reaches 92.8% of the theoretical value. Compared with Comparative Example 1, it can be seen that doping with 5wt% VNbO5 can reduce the initial dehydrogenation temperature of MgH2 from 322.2°C to 202.6°C, a decrease of 119.6°C; compared with Example 1, it can be seen that increasing the VNbO5 doping amount can reduce the initial dehydrogenation temperature from 202.6°C to 200.2°C, a decrease of 2.4°C. The initial dehydrogenation temperature of the hydrogen storage material in Example 4 is 195°C. When the temperature is raised to 400°C, the dehydrogenation amount is 6.611wt%, and the dehydrogenation rate reaches 87% of the theoretical value. Compared with Comparative Example 1, it can be seen that doping with 10wt% VNbO5 can reduce the initial dehydrogenation temperature of MgH2 from 322.2°C to 195°C, a decrease of 127.2°C; compared with Example 1, it can be seen that increasing the VNbO5 doping amount can reduce the initial dehydrogenation temperature from 200.2°C to 195°C, a decrease of 5.2°C.

[0098] At different target dehydrogenation temperatures and different target absorption temperatures, isothermal dehydrogenation tests and isothermal absorption tests were performed on the hydrogen storage materials of Example 1 and Comparative Example 1 to analyze the hydrogen absorption and dehydrogenation kinetics of the materials. When the target dehydrogenation temperatures of the isothermal dehydrogenation tests were 250°C, 265°C, 275°C, 300°C and 325°C, respectively, the test results are as follows: Figure 5As shown. Under the conditions of target dehydrogenation temperature of 300°C and dehydrogenation time of 60min, the dehydrogenation amount of the hydrogen storage material of Comparative Example 1 is 0.536wt%, and the dehydrogenation amount of MgH2 can be significantly increased from 0.536wt% to 6.45wt% by adding VNbO5 in Example 1. The isothermal dehydrogenation test results show that the dehydrogenation amount of the hydrogen storage material at 300°C in 5.06min reaches 6wt%, the dehydrogenation amount reaches 6.45wt% in 60min, and the dehydrogenation amount at 250°C in 60min can also reach about 3wt%.

[0099] The isothermal hydrogen absorption diagrams of the hydrogen storage materials of Example 1 and Comparative Example 1 at different temperatures (100°C, 125°C, 150°C, 175°C and 200°C) are shown in FIG. Figure 6 The isothermal hydrogen absorption test results show that under the conditions of target dehydrogenation temperature of 200°C and hydrogen absorption time of 60 minutes, the hydrogen absorption amount of the hydrogen storage material of Comparative Example 1 is 3.0wt%. By adding VNbO5, Example 1 can significantly improve the hydrogen absorption amount of MgH2. Under the temperature conditions of 125°C, 150°C, 175°C and 200°C, it can absorb more than 90wt% of H2 in a very short time. At a lower temperature of 100°C, it can absorb 4.66wt% of H2 within 60 minutes.

[0100] The cyclic performance test of the hydrogen storage material of Example 1 was carried out to analyze its stability. The specific test method of the cyclic performance test is to alternately carry out 20 isothermal hydrogen release tests and isothermal hydrogen absorption tests under the target hydrogen release conditions of 300°C and the target hydrogen absorption conditions of 300°C and 3MPaH2. The isothermal desorption / adsorption cycle curve of the hydrogen storage material prepared in Example 1 is as follows: Figure 7 As shown, the red line represents the isothermal hydrogen release curve, and the blue line represents the isothermal hydrogen absorption curve. After analysis, it can be seen that after 20 cycles, the actual hydrogen absorption / dehydrogenation capacity of the hydrogen storage material remains at 6.691wt% / 6.65wt%, and compared with the capacity of the first cycle, the capacity retention rate is 95.3% / 99.86%.

[0101] At different heating rates, the hydrogen storage materials of Example 1 and Comparative Example 1 were subjected to DSC tests to analyze the hydrogen release kinetic activation energy of the materials. The DSC curves of the hydrogen storage materials of Example 1 and Comparative Example 1 and the peak fitting diagrams of the DSC curves are shown in FIG. Figure 8As shown. The DSC spectra of the hydrogen storage material at heating rates of 2°C / min, 5°C / min, 8°C / min and 10°C / min all show two endothermic peaks, which is presumably caused by the uneven contact between MgH2 and VNbO5 during the ball milling process. According to the measured DSC curve and the Kissinger equation, the dehydrogenation activation energies of the hydrogen storage materials of Example 1 and Comparative Example 1 are calculated to be 75.32 kJ / mol and 145.25 kJ / mol, respectively, and the dehydrogenation activation energy of the composite material is significantly lower than that of MgH2.

[0102] The present invention performs fitting based on the isothermal hydrogen absorption curves measured at different temperatures, combined with the JMA (Johnson-Mehl-Avrami) equation and the Arrhenius equation, to analyze the hydrogen absorption kinetic activation energy of the material. The JMA curve and Arrhenius fitting curve of the hydrogen storage material of Example 1 and Comparative Example 1 are as follows: Fig. 9 As shown, according to calculation, it can be known that the hydrogen absorption activation energy of the hydrogen storage material prepared in Example 1 and pure MgH2 is 54.4 kJ / mol and 79.1 kJ / mol respectively. Compared with the MgH2 of Comparative Example 1, the hydrogen absorption activation energy of the hydrogen storage material prepared in Example 1 is greatly reduced.

[0103] The present invention integrates the peak area of ​​the measured DSC data to explore the dehydrogenation thermodynamic enthalpy change of the prepared hydrogen storage material. The DSC graphs of the hydrogen storage materials of Example 1 and Comparative Example 1 are as follows: Fig.10 As shown, the calculation shows that the dehydrogenation enthalpy change of the hydrogen storage material is ΔH = 73.26 kJ / mol, and the dehydrogenation enthalpy change of MgH2 after ball milling is ΔH = 76.73 kJ / mol. Analysis shows that the change in the dehydrogenation enthalpy change is not large. It can be seen that the addition of the catalyst slightly reduces the enthalpy change of the MgH2 dehydrogenation reaction, but hardly changes the thermodynamic properties of the system, indicating that the decomposition path of MgH2 has not been changed, but it simply acts as a catalyst to improve the dehydrogenation performance of MgH2.

[0104] The performance test results of the hydrogen storage materials prepared in the above examples and comparative examples are shown in Table 1.

[0105] Test method:

[0106] Hydrogen desorption temperature: The test was carried out at a heating rate of 2°C / min.

[0107] Hydrogen absorption rate: tested at 100°C and 30 bar.

[0108] Hydrogen release rate: tested at 300°C and 0.01 bar.

[0109] Cyclic stability: tested at 300°C, hydrogen absorption pressure 30 bar, and hydrogen desorption pressure 0.01 bar.

[0110] Table 1

[0111]

[0112] The above experimental results show that the addition of VNbO5 significantly reduces the dehydrogenation temperature of MgH2. After adding 3wt% VNbO5, the initial dehydrogenation temperature of MgH2 decreased from 322.2℃ to 206.3℃, which was 115.9℃ lower than that of the ball-milled MgH2 sample. Further increasing the amount of catalyst added, the dehydrogenation temperature of the sample also decreased, but the temperature drop was small. When the addition amount was further increased to 10wt%, although the initial dehydrogenation temperature was further reduced, the effective hydrogen storage capacity of the system was reduced. Comprehensively comparing the dehydrogenation temperature, dehydrogenation amount and dehydrogenation rate, MgH2-7wt% VNbO5 hydrogen storage material has the best dehydrogenation performance. Its initial dehydrogenation temperature is 122℃ lower than that of the ball-milled MgH2, the total amount of dehydrogenation is 7.02wt%, and the dehydrogenation rate reaches 92.4% of the theoretical value.

[0113] It can be seen from the above that, compared with the comparative example, in the hydrogen storage materials of each embodiment of the present invention, MgH2 and the fibrous bimetallic oxide VNbO5 cooperate with each other, which not only effectively improves the hydrogen desorption kinetics of MgH2, reduces the hydrogen desorption temperature of magnesium hydride, and increases the hydrogen desorption rate of MgH2, but also effectively improves the hydrogen absorption kinetics of MgH2, increases the hydrogen absorption rate of MgH2, and the fibrous VNbO5 can form a good contact with MgH2, effectively improving the catalytic effect and cycle stability of the hydrogen storage material.

[0114] In addition, it can be seen that when all process parameters are within the preferred range of the present invention, the hydrogen storage material has a lower dehydrogenation temperature, a faster hydrogen absorption and dehydrogenation rate, better cycle stability, and a better catalytic effect of the catalyst.

[0115] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A hydrogen storage material, characterized in that: The invention comprises MgH2 and fibrous VNbO5, wherein the aspect ratio of the fibrous VNbO5 is 5.0×10 4 ~1.15×10 5 .

2. The hydrogen storage material according to claim 1, characterized in that The diameter of the fibrous VNbO5 is 300 to 1000 nm, preferably 300 to 500 nm; and / or, The specific surface area of ​​the fibrous VNbO5 is 89 to 96 m 2 / g.

3. The hydrogen storage material according to claim 1 or 2, characterized in that: In the hydrogen storage material, the weight percentage of the fibrous VNbO5 is 3-10%.

4. The hydrogen storage material according to any one of claims 1 to 3, characterized in that When the aspect ratio of the fibrous VNbO5 is 5.0×10 4 ~7.35×10 4 When the weight percentage of the fibrous VNbO5 in the hydrogen storage material is 5-7%.

5. The hydrogen storage material according to any one of claims 1 to 4, characterized in that The hydrogen storage material is heated to release hydrogen, with the initial hydrogen release temperature being 195-200.2° C.; The hydrogen storage material is subjected to isothermal hydrogen release, and under the condition that the hydrogen release temperature is 250 to 325° C., the hydrogen release rate is 1.01 to 1.62 wt % / min; The hydrogen storage material is subjected to isothermal hydrogen absorption, and under the condition that the hydrogen absorption temperature is 75 to 125° C., the hydrogen absorption rate is 0.298 to 0.354 wt % / min; After the hydrogen storage material is subjected to 20 cycles of isothermal hydrogen release and 20 cycles of isothermal hydrogen absorption at 300° C., the hydrogen absorption capacity retention rate is 91.6-95.3%, and the dehydrogenation capacity retention rate is 93.3-99.86%.

6. The method for preparing the hydrogen storage material according to any one of claims 1 to 5, characterized in that: The following steps are involved: Step S1, first mixing a vanadium source, a niobium source and a co-solvent, and sequentially spinning and calcining to obtain fibrous VNbO5; Step S2, ball milling MgH2 and the fibrous VNbO5 to obtain the hydrogen storage material.

7. The preparation method according to claim 6, characterized in that: In the step S1, The vanadium source includes one or more of ammonium metavanadate, vanadium pentoxide and vanadium acetylacetonate; and / or, the niobium source includes one or more of niobium oxalate, niobium pentoxide and niobium pentachloride; and / or, The co-solvent comprises one or more of oxalic acid, citric acid and acetic acid; and / or, The molar ratio of the vanadium source, the niobium source and the co-solvent is 1:(0.8-1.2):(0.8-1); Preferably, the step S1 further comprises: performing a second mixing of the vanadium source, the niobium source and the co-solvent, and then performing a third mixing with a solvent and a stabilizer to obtain a mixed gel, and sequentially performing the spinning and calcining of the mixed gel; more preferably, the solvent comprises one or more of water, ethanol, methanol and N,N-dimethylformamide; and / or the stabilizer comprises one or more of PVP, polyvinyl acetate and polyacrylonitrile; further preferably, the solid content of the mixed gel is 8 to 11 wt%.

8. The preparation method according to claim 6 or 7, characterized in that: In the step S1, the spinning is electrostatic spinning; Preferably, the electrospinning liquid pushing speed is 0.08 to 0.12 mm / min, the applied positive voltage is 18 to 22 kV, the applied negative voltage is -1 to -3 kV, and the receiving distance is 12 to 18 cm.

9. The preparation method according to any one of claims 6 to 8, characterized in that: In the step S1, The calcination temperature is 500-550° C. and the calcination time is 3-5 hours.

10. The preparation method according to any one of claims 6 to 9, characterized in that: In the step S2, The ball milling pressure is 0.3-0.8 MPa; and / or, The ball-to-material ratio of the ball mill is (40-60):1; and / or, The ball mill has a rotation speed of 400-450 rpm and a milling time of 5-10 hours.